Comparison of Essential Oil of Lemongrass (Cymbopogon Citratus) Extracted with Microwave-Assisted Hydrodistillation (MAHD) and Conventional Hydrodistillation (HD) Method - Ranitha, Mathialagan; Nour, A. H.; Ziad, A.S; Azhari, H. Nour; Thana, Raj. S. (AENSI Publishing, 2014)
The increasing demand of essential oil has opened up wide opportunities for global marketing which leads to the requirement of its competitive product in market that comes with all the advantages in term of cost, quality and its production time. Microwave-assisted hydrodistillation (MAHD) method is an advance extraction technique that takes advantage of microwave heating with the conventional hydrodistillation (HD). This research was carried out to study the effect of different MAHD parameters which were water to plant material ratio (6:1, 8:1,10:1), microwave power (200 W,250W) and extraction time (30min,60min, 90min,120min) in extraction of essential oil from Lemongrass (Cymbopogon Citratus). Its extraction yield and major constituents were analyzed and the results were compared with those of conventional HD. The optimum parameters were found at water to plant material ratio of 8:1, microwave power of 250W and 90 minutes of extraction and the yield obtained under this condition was 1.46%. The gas chromatography/mass spectrometric (GC-MS) analysis showed that the content of main constituents which were neral, geranial and myrcene were almost similar in the essential oil extracted using MAHD and conventional HD. This has proved that the use of microwave irradiation did not adversely influence the composition of essential oils. Overall, the results obtained indicate that MAHD method provided a good alternative for the extraction of essential oil from Lemongrass (Cymbopogon Citratus).